Students and Teachers’ Attitudes towards the effectiveness of Distance Education during Covid-19 Pandemic: Egypt and Morocco as case study - Boukranaa, Ahmed Mohammed; Mjahad, Rania Abdasalam; Mohammed , Rabah EIsayed (Technium Social Sciences Journal, 2023)
Within a few years, the distance education platforms have emerged to attain a valuable presence in higher education institutions especially during Coronavirus. During the pandemic most of the countries declared a state of emergency which resulted in the suspension of face to face learning in all the educational institutions. Universities around the world were obliged to shift from traditional classrooms to virtual ones using different tools and technologies. This study aims at investigating the effectiveness of distance education through highlighting the attitudes of both students and teachers. To draw logical conclusions about the effectiveness of distance education in Morocco and Egypt, two major approaches are used qualitatively that took the form of online interviews with university teachers to detect their attitudes towards distance learning. Also, a quantitative that took the shape of a questionnaire to evaluate the experience of students with distance education during the pandemic in both countries.